Architects of infinity - Beyer, Kirsten (Star trek, voyager (Series), 2018)
While investigating a planet on which a new element has been discovered, Admiral Kathryn Janeway and the crew of the Starship Voyager learn that it could be home to a species with tremendous power to reshape the galaxy.